Psychological well-being among broken home young adults: The role of social anxiety disorder and hardiness - Helen Natalie; Jessica Christina Widhigdo (Humanitas: Indonesian Psychological Journal, 2024)
In Indonesia, 448.126 divorce cases were reported in 2023. Losing parent(s) as a consequence of parental divorce or death results in children becoming broken-home. In the absence of a parent figure, children experience harmful psychological effects, including ongoing social anxiety until they become young adults. This may disrupt young adults’ developmental task to form intimacy hence leading to poor psychological well-being. Young adults from broken home families must possess hardiness to cope with daily stress and traumatic experiences. Therefore, this study aimed to investigate the role of social anxiety disorder and hardiness in psychological well-being among broken-home young adults. Participants of this study were 200 young adults with broken-home family. The scales used were The Indonesian version of the Psychological Well-being Scale, The Social Phobia Inventory (SPIN), and the DRS-15 Dispositional Resilience Scale. Data was analyzed using the Multiple Regression Model. The results showed that there was a significant contribution of social anxiety disorder and hardiness on psychological well-being, with a total contribution of 53.8 percent. It is recommended for future interventions to detect social anxiety disorder potency, as well as to include hardiness variable in optimizing psychological well-being quality, especially in broken-home young adults.